Moth Variation using 3 Kinds of Pineapple, Banana, and Tapai as Bait in Liwa Botanical Garden - Kinanti, Astrid Febi; Nukmal, Nismah; Pratami, Gania Dania; Kanedi, M. (Jurnal Natur Indonesia, 2020)
Moths are insects that belong to the Lepidoptera Ordo. Moths are attracted to volatile compounds. The examples of volatile compounds include alcohol, urea, and acetic acid. Pineapple, banana and tapai are three types of bait that will be used in this study, because all three types of bait contain volatile compounds in the form of scents that strong enough to attract moths. Liwa botanical garden is a recreational and educational place, located in West Lampung district, which was only approved by the Regional Government in 2007. Because there is onlya view data on the presence of moths, so it needs to conduct the research to know the variation types of moths that exist in Liwa botanical garden, West Lampung. This research is a Quasy Experiment with 3 kinds of baits, there are pineapple, banana, and tapai as a treatment with 5 replications in the form of sampling time. The result obtained that in AraceaeLiwa Botanical Garden were obtained by six families, nine genera, and nine species of moth. Nine species of moths are Nemophora sp, Nematopogon sp, Brahmaeawallichii, Rhodogastriaamasis, Creatonosgungis, Sundasceliaepelys, Rheumaptera sp, Noctua sp, and Epicnopterix sp